Histopathological analysis of skin adnexal tumors: An experience at a tertiary center - Gokhan Sahin; Seda Koc Sahin (Indian Journal of Pathology and Microbiology, 2024)
Background: Skin appendage tumors (SATs) are benign and malignant neoplasms. Although there are many studies on their clinical features and epidemiology in the literature, most of these studies have a small number of patients and are not classified according to the WHO 2018 classification. Objectives: This study aimed to reveal the clinical and histopathological features of the SATs and compare the pre-diagnosis. Materials and Methods: Cases diagnosed with SATs in the last 7 years in the Pathology Department were re-evaluated according to the WHO 2018 classification. Patients’ ages and genders, as well as the location and pre-diagnosis of the lesion, were all recorded. Results: A total of 437 patients, 198 (45.3%) male and 239 (54.7%) female, were included in the study. Of 437 patients, 399 (91.3%) were diagnosed with benign SATs and 38 (8.7%) were diagnosed with malignant SATs. Most of the cases were benign tumors with follicular differentiation. Malignant SATs were seen in patients significantly older than benign ones. The majority of SATs were in head and neck localization. Mammary Paget’s disease was the most common malignant SAT (n = 14, 36.8% of patients diagnosed with malignant SATs). It was noted that clinicians were less likely to consider a specific diagnosis of SAT before excision. Conclusion: SAT, a diagnosis that can be seen at any age and is difficult to predict clinically, may be malignant, especially in elderly patients. Histopathology is the gold standard in diagnosing SATs, and immunohistochemical staining may be useful in diagnosing tumors with uncertain histopathological features.